Diagnostic accuracy of serum inflammatory markers in late fracture-related infection: a systematic review and meta-analysis. (December 2018) - van den Kieboom, J.; Bosch, P.; J. Plate, J. D.; A. IJpma, F. F.; Kuehl, R.; McNally, M. A.; Metsemakers, W-J.; M. Govaert, G. A.
Abstract : Aims: To assess the diagnostic value of C-reactive protein (CRP), leucocyte count (LC), and erythrocyte sedimentation rate (ESR) in late fracture-related infection (FRI). Materials and Methods: PubMed, Embase, and Cochrane databases were searched focusing on the diagnostic value of CRP, LC, and ESR in late FRI. Sensitivity and specificity combinations were extracted for each marker. Average estimates were obtained using bivariate mixed effects models. Results: A total of 8284 articles were identified but only six were suitable for inclusion. Sensitivity of CRP ranged from 60.0% to 100.0% and specificity from 34.3% to 85.7% in all publications considered. Five articles were pooled for meta-analysis, showing a sensitivity and specificity of 77.0% and 67.9%, respectively. For LC, this was 22.9% to 72.6%, and 73.5% to 85.7%, respectively, in five articles. Four articles were pooled for meta-analysis, resulting in a 51.7% sensitivity and 67.1% specificity. For ESR, sensitivity and specificity ranged from 37.1% to 100.0% and 59.0% to 85.0%, respectively, in five articles. Three articles were pooled in meta-analysis, showing a 45.1% sensitivity and 79.3% specificity. Four articles analyzed the value of combined inflammatory markers, reporting an increased diagnostic accuracy. These results could not be pooled due to heterogeneity. Conclusion: The serum inflammatory markers CRP, LC, and ESR are insufficiently accurate to diagnose late FRI, but they may be used as a suggestive sign in its diagnosis.